Motivasi Calon Pekerja Migran Indonesia Bekerja ke Luar Negeri dan Kontribusinya Bagi Negara Indonesia: (Skema Penempatan Korea Selatan) - Sembada, Andhika Djalu; Prasetyo, Danang; Yarmanto, Yarmanto (Jayapangus Press, 2024)
Fulfilment of the needs of a decent life and the desire to change their fate are the main highlights in the choice of Indonesian citizens to decide to work abroad. In line with this, there is a positive response from the employer country regarding the demand for Indonesian labour. The research method used is narrative qualitative by conducting a data collection process carried out twice when prospective Indonesian migrant workers (CPMI) carry out OPP (Pre-departure Orientation) activities before heading to South Korea. The first data collection was conducted on 27 January-1 February 2023 which took place in Surabaya which was a mixture of new CPMIs and CPMIs who had previously left. The research findings are that there are stages that must be passed by CPMI before leaving for South Korea, one of these stages is OPP. During the implementation, 89 participants were interviewed with questions about the underlying motivation to work abroad. The answer was 73% answering money as the main reason as well as motivation to be able to live decently. Another impact apart from a decent living felt by CPMI is the contribution to the country. In the second quarter of 2023, the contribution to the country reached IDR 77.35 trillion. This is certainly a positive achievement whose impact can be felt both by citizens and the Indonesian state. Migrant workers make investments from the income saved to build businesses, renovate houses, pay debts, buy assets in the form of land, to the education of migrant workers' families. Some also actively empower the surrounding community in running their business, so that it automatically has a major contribution to poverty reduction in Indonesia by encouraging economic growth.